2017
DOI: 10.1080/10942912.2017.1315589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatile compounds in Antarctic krill (Euphausia superba) using headspace solid-phase microextraction and GC-MS

Abstract: Antarctic krill (Euphausia superba) has a very high economic value due to its enormous production, higher protein content, and nutritional value. This study presents a detailed optimization of the analysis of volatile flavor compounds from Antarctic krill by combining headspace solid-phase microextraction (HS-SPME) as the extracting method and gas chromatography/ mass spectrometry (GC-MS) as the analysis. An optimal solid-phase microextraction (SPME) fiber was selected, and the microextraction conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Krill extract is a mixture of various individual chemicals that could be detected by the whales’ chemoreceptors. A chemical analysis carried out on homogenized Antarctic krill samples showed that it contains several classes of volatile compounds that could be ligands for the whales’ olfactory receptors, including esters, aldehydes, ketones, pyrazines, hydrocarbons as well as DMS [65]. We also expect it to include a significant amount of peptides and amino acids since the krill used in our experiments is an enzymatic (subtilisin EC 3.4.21.14) hydrolysate.…”
Section: Discussionmentioning
confidence: 99%
“…Krill extract is a mixture of various individual chemicals that could be detected by the whales’ chemoreceptors. A chemical analysis carried out on homogenized Antarctic krill samples showed that it contains several classes of volatile compounds that could be ligands for the whales’ olfactory receptors, including esters, aldehydes, ketones, pyrazines, hydrocarbons as well as DMS [65]. We also expect it to include a significant amount of peptides and amino acids since the krill used in our experiments is an enzymatic (subtilisin EC 3.4.21.14) hydrolysate.…”
Section: Discussionmentioning
confidence: 99%
“…6-Methyl-5-hepeten-2-one contributes to the lemongrass aroma [42] . Furans and pyrazines have nutty and roasted aromas [43] . 2-Pentyl-furan is the only furan identified in SFC, with a beany and grassy aroma.…”
Section: Resultsmentioning
confidence: 99%
“…It is also the major aroma compound occupying 32.5 % of the total volatile concentration, followed by naphthalene (17.5 %), an aromatic hydrocarbon with a camphor-like odor. However, based on TAV, nonanal is the major odor-contributing compound next to 3-ethyl-2,5-dimethylpyrazine, which smells like fat and citrus [43] . Four short-chain acids were identified in SFC, among which heptanoic acid is the major, followed by acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The suitability of a particular fiber coating for a specific analyte is related to the polarity of the extraction phase and the overall selectivity toward the analyte over other matrix components. [17] A considerable number of VOC-analysis studies using CAR/PDMS fibers have been reported with the aim of assessing vinegar quality. Mejıas et al [12] reported that the CAR/PDMS fiber exhibited better performance for determining acetates, alcohols, and aldehydes in Chinese vinegars compared to DVB/PDMS or PDMS fibers.…”
Section: Resultsmentioning
confidence: 99%